Speech by the hon'ble minister for welfare services on the Occasion of the opening of the PO LEUNG KUK handicraft sales centre in Penang on 30th November 1972. - Hashim, Fatimah (1972)
I am glad to be here this evening on the occasion of the opening of the Handicraft Sales Centre.This Sales Centre marks another successful step in the progress and achievements of the Po Leung Kuk Home Committee so ably led by you, Mr. Chairman.